If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 77 + -1x = 0 Solving 77 + -1x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-77' to each side of the equation. 77 + -77 + -1x = 0 + -77 Combine like terms: 77 + -77 = 0 0 + -1x = 0 + -77 -1x = 0 + -77 Combine like terms: 0 + -77 = -77 -1x = -77 Divide each side by '-1'. x = 77 Simplifying x = 77
| 3x^3-40x^2+97x+10=0 | | 65=2x+3x-10 | | 6n=1+4n+19 | | 2sec^2x=3-tanx | | 3-21y-24y^2=0 | | X/2=2x-1/3 | | 30x/5+15x/3=15 | | -r^3t-rt^3=0 | | 3x^2-6y=0 | | 5=7x+3 | | 5x+30=20 | | 14x^2+33x+10=0 | | 24=18/x | | 14b-10= | | -5x+40=6x-60 | | 2(10)=24-2(10) | | -4=4v | | 88=x+x-6 | | -x=-77 | | X+2x-5=0 | | 10=24-2(10) | | 3f=-3+12 | | x+x-6=88 | | 400=0.14+2 | | x-6+x=88 | | 6x/3+7/15x+3 | | (x-8)/(-x+77)=2 | | 5(x+3)=-5 | | y=42+-5y | | -1.14*23.25+47= | | y=0.63(0.5)x | | 3/8x-8=-7 |